Pravica do stavke v vojaški organizaciji - Štampar, Ljubo (Teorija in praksa, 2015)
The Constitutional Court of the Republic of Slovenia adopted a requirement for a constitutional review with respect to the prohibition on the right to strike for the Slovenian Armed Forces. In most EU member states, the right to strike in the army is denied due to issues of efficiency and alternative loyalty. Through analysis, we find that the trend of the increasing similarity of military and civilian professions also requires a similar regulation of relations between the army and soldiers in connection with the work, as is the case in civil society. The analysis shows that the EU takes three different approaches to the coordination of relations between the army and soldiers in connection with work. Only one of them includes the right to strike, and four members of the EU successfully practise it. European institutions defend the concept that the soldier is a "citizen in uniform" and enjoys all the rights enjoyed by other citizens. In conclusion, we are opening up a debate on whether the request for the review of constitutionality has any chances of success in the circumstances under study.
Keywords: človekove pravice; European Union; Evropska unija; human rights; Labor unions; Military organization; Sindikati; Slovenia; Slovenija; Stavke; Strikes; Vojaška organizacija